Effectiveness of lower limb arterial angioplasty - Szuciak, Anna; Talarek, Konrad; Szewczyk, Julia; Świta, Michał; Skierkowski, Bartosz; Drelichowska, Alicja; Ciszewski, Przemysław; Azierski, Michał; Pikor, Damian (Quality in Sport, 2024)
Introduction: Over 200 million individuals worldwide suffer with peripheral artery disease (PAD). The disease makes it difficult to function properly by limiting walking and physical activity, which also translates into a reduced quality of life. Purpose of the Study: The purpose of this review is to evaluate the effectiveness of lower limb angioplasty as a treatment to restore arterial patency, improve the patient's quality of life and reduce complications. Methodology: A comprehensive search of databases was conducted from 2016, using PubMed, Scopus and Google Scholar, using keywords such as ”angioplasty”, “peripheral artery disease”, “revascularization”, “endovascular intervention”, “atherosclerosis, “quality of life”. Results: Angioplasty and bypass surgery showed comparable amputation-free survival at two years, though bypass surgery improved overall survival by approximately seven months. Bypass surgery had significantly higher rates of infection compared to angioplasty, leading to increased hospital stays and associated costs. Socioeconomic status significantly influenced outcomes, with lower status relating to higher amputation rates. No significant superiority was observed between bypass surgery and angioplasty in many studies, though treatment choice should be guided by patient condition. Conclusions: Angioplasty is a safe and effective way to treat PAD can help alleviate the growing global burden of the disease and reduce bed occupancy and improve productivity.